The Role of Trust Mediation in Influencing Purchase Decisions: A Case study of the Influence of Augmented Reality, Customer Ratings, and Customer Reviews on E-Commerce Platforms - Subagja, Yayang Maulud; Kusmiati, Eti (Yayasan Sinergi Kawula Muda, 2026)
The research investigates Trust mediation effects which link Augmented Reality to Customer Rating and Customer Review and their combined impact on e-commerce purchase decisions. This study analyzes the gap between physical and digital products in e-commerce, which causes significant order cancellations due to mismatched representations. Zhang et al. (2023) found that 45% of cancellations among e-commerce users in Southeast Asia were caused by product appearance discrepancies such as color, texture, or dimensions, while Forrester (2023) found that 55% of global consumers doubt the credibility of online reviews due to suspected manipulated feedback. The novelty of this research lies in the integration of AR technology and social signals with trust as mediates in the specific context of the e-commerce market in Indonesia. Utilizing PLS-SEM on 246 purposively sampled respondents, all primary paths proved statistically significant. Key findings show positive impacts of AR, customer ratings, and reviews on purchase decisions, with trust as empirical mediator. Practically, e-commerce practitioners must integrate AR and ensure feedback transparency to strengthen consumer trust.